Ozone-Induced Kinetic Deactivation of Aspergillus flavus in Nutmeg Seed (Myristica fragrans Houtt) - Hendra Adi Prasetia; Francis Maria Constance Sigit Setyabudi; Rini Yanti; Chusnul Hidayat (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Aspergillus flavus is a fungal species frequently contaminating nutmeg seeds. Therefore, this study aimed to prevent sporulation by introducing gaseous ozone treatment. In the process, spore suspensions (4.8 x 10 7 spore/ mL) were exposed to ozone (0-11 ppm) for 90 min. Approximately 0.5 mL of each suspension was plated on CDA and incubated at 28 °C (7 days; 24 hours for the remaining samples) alongside the remaining 4.5 mL for 24-60 hours. The results showed that the treatment has significantly delayed the spore germination up to 60 hours. A positive correlation exists between the increasing gas concentration and the lowering of germination. Furthermore, the reduction of A. flavus load after being treated was from 0.24-1.2 log spores/mL. The efficacy of this treatment is directly proportional to the concentration of ozone. The three proposed models, including the linear log regression, the Geeraerd shoulder, and the Weibull models, were fully suitable for describing spore inactivation kinetics, emphasizing the potential of ozone as an effective antifungal treatment for microbial control.